PENGARUH PERBEDAAN SUHU PENGERINGAN TEPUNG TAPAI UBI KAYU TERHADAP MUTU FISIK DAN KIMIA YANG DIHASILKAN - Eka Lidiasari; Merynda Indriyani Syafutri; Friska Syaiful (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
The objective of the research was to determine the influence of drying temperature on physical and chemical characteristics of partially fermented cassava flour. The research was conducted in Agriculture Product Chemical Laboratory of Agriculture Technology Department, Sriwijaya University, Indralaya. The research used case study. Measurement of physical and chemical characteristics of partially fermented cassava flour were conducted with two replications. The result showed that colour of partially fermented cassava flour dried on 70 and 80 oC was yellow reddish, but colour of partially fermented cassava flour dried on 70 oC was more lightness. The capacity of water absorption, ash content, starch content and protein content of partially fermented cassava flour dried on 70 oC were higher than that of 80 oC. Whereas the moisture content and total acid content of partially fermented cassava flour dried on 80 oC were higher than that of 70 OC.